A Better Estimate of Internally Generated Intangible Capital - Iqbal, Aneel; Rajgopal, Shiva; Srivastava, Anup; Zhao, Rong (Management Science, 2024)
Internally developed intangibles are not included in reported assets under U.S. generally accepted accounting principles. The omission of this increasingly important class of assets reduces the usefulness and relevance of financial statement analysis, conducted with reported values of equity and assets. Recent studies overcome this deficiency by capitalizing research and development (R&D) expenses to estimate the value of knowledge capital and by capitalizing selling, general, and administrative (SG&A) expenses to estimate the value of organization capital. Those two estimates are then added to reported values for financial statement analysis. For convenience, many studies rely on two rules of thumb and assume them to be equally applicable in all instances: (1) 30% of SG&A and 100% of R&D expenses are investments, and (2) the useful life of SG&A and R&D investments is three and five years, respectively. We propose a more flexible approach by estimating the capitalization and amortization parameters on an industry–year–specific basis. Our modified values of total assets and equity, inclusive of the value of capitalized intangibles, exhibit greater association with future returns and investments compared with as-reported values and values estimated with uniform rules of thumb. We provide a better estimate of intangible capital for the consumers of financial statements. This paper was accepted by Ranjani Krishnan, accounting. Funding: A. Srivastava and R. Zhao acknowledge financial support from the Social Sciences and Humanities Research Council of Canada. A. Srivastava acknowledges financial support from the Canada Research Chairs Program of the Government of Canada. A. Iqbal acknowledges financial support from the Canadian Securities Institute Research Foundation and Chartered Professional Accountants (Alberta) Education Foundation. Supplemental Material: The data files are available at https://doi.org/10.1287/mnsc.2022.01703 .